Method for measuring concentration of metaldehyde in dendrobium

Through the combination of terahertz sensor and metal-graphene metamaterial, the terahertz wave incident detection of tetrameraldehyde concentration is solved, and the problem of complex and low efficiency detection in the prior art is achieved, and high sensitivity and fast tetrameraldehyde Concentration detection.

CN119269441APending Publication Date: 2025-01-07WEST ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411460461.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art requires complex testing conditions and cannot be detected quickly in determining the concentration of tetraacetaldehyde in Dendrobium, resulting in insufficiency of detection.

Method used

The terahertz sensor based on FSRRs is used to test the resonant characteristics of the metamaterial through the THz-TDS system, and combined with the metal-graphene metamaterial sensor, the concentration changes of tetrameracetaldehyde are detected by terahertz wave incident to achieve accurate detection.

Benefits of technology

The sensitivity of tetrameracetaldehyde detection is improved, and the detection limit reaches 100ng/mL, simplifying the detection process and improving the detection efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119269441A_ABST
    Figure CN119269441A_ABST
Patent Text Reader

Abstract

The invention discloses a method for determining the concentration of metaldehyde in dendrobium nobile, and relates to the technical field of metaldehyde concentration determination. The method for determining the concentration of metaldehyde in dendrobium nobile comprises the following specific steps: dropwise adding a plurality of groups of 20 [mu] L metaldehyde solutions with different concentrations to the central position of a detection sensor by using a pipette, standing in air for 15-20 min, and waiting for the metaldehyde solution to dry and evaporate on the surface of the sensor until a film is formed, and depositing on an area of 8 * 8 mm < 2 > to form an FSRRs-based sensor, and accurately detecting the concentration of metaldehyde by analyzing the relationship between metaldehyde with different concentrations and formants. The problems that a traditional detection method is complex in treatment and rapid detection cannot be achieved are solved, the metal-graphene mixed type element sensor is adopted as a carrier, the sensitivity of problem detection is achieved through the terahertz technology, and the detection limit reaches 100 ng / mL.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metaldehyde concentration determination, in particular to a method for determining the metaldehyde concentration in dendrobium. Background Art

[0002] Dendrobium nobile Lindl, also known as Golden Hairpin Dendrobium, Golden Hairpin Flower, Millennium Run, etc., is a plant of the genus Dendrobium in the family Orchidaceae. Dendrobium stems are erect, fleshy, thick, slightly flat and cylindrical. The leaves are leathery and oblong. The racemes emerge from the middle part of the old stem with leaves or fallen leaves. The petals are more or less oblique and broadly ovate, with green stamens and columns, and the cap is purple-red and conical. The fruit of Dendrobium is a capsule, which is oblong or pear-shaped, with small and numerous seeds. Dendrobium is distributed in China, India, Nepal and other places. In China, it is mainly distributed in subtropical areas such as Taiwan, Fujian, and Hunan. Dendrobium likes warm, humid and relatively cool environments, and often grows with mosses. It is suitable for growing on tree trunks in mountain forests or on rocks in valleys.

[0003] However, from March to November, snails will infest the tender stems and leaves, thus affecting the growth and yield of Dendrobium. At this time, farmers will spray pesticides containing metaldehyde, but if the content of metaldehyde is too high, it will cause human discomfort or even death. Therefore, pesticide residue detection is of great significance to the product quality and safety of Dendrobium.

[0004] The prior art often uses gas chromatography to determine metaldehyde. This method requires the establishment of a large number of test conditions for the determination of metaldehyde, including but not limited to support, chromatographic column, detector, temperature, carrier gas, injection volume, bridge current, sensitivity and paper speed. Although it is accurate and has a very low measurement limit, the preparatory work is extremely complicated and rapid detection is impossible. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a method for determining the concentration of metaldehyde in Dendrobium officinale, which solves the problems raised in the above-mentioned background technology.

[0006] To achieve the above object, the present invention is implemented by the following technical scheme: a method for determining the concentration of metaldehyde in Dendrobium officinale, comprising the following specific steps:

[0007] S100: Use a pipette to drop 20uL of several groups of metaldehyde solutions with different concentrations onto the center of the detection sensor and leave it in the air for 15-20 minutes, waiting for the metaldehyde solution to dry and evaporate on the sensor surface until a thin film is formed and deposited on the 8×8mm 2 On the FSRRs-based sensor formed on the area;

[0008] S200: Test the resonance characteristics of the metamaterial on the sensor through the THz-TDS system. Fix the sensor in the measurement chamber, open the nitrogen valve to dry the measurement chamber, wait for 5-10 minutes, and then scan to obtain the characteristic spectrum of the transmission amplitude.

[0009] S300: By analyzing the relationship between metaldehyde and resonance peak at different concentrations, the concentration of metaldehyde can be accurately detected;

[0010] S400: After each concentration measurement, the metamaterial in the corresponding sensor was soaked in acetone for 10 min to wash away the residual metaldehyde, soaked in anhydrous ethanol for 10 min to wash away the acetone, then rinsed with deionized water for 10 min to wash away the ethanol, and finally dried in a nitrogen-filled environment for the next test.

[0011] A further improvement of the technical solution of the present invention is that in order to specifically detect the concentration of metaldehyde, the sensor preparation process includes the following specific steps:

[0012] Q100: Use CSTM icrowaveStud io software to design a sensor metamaterial model and use the software to perform simulations to obtain the optimal solution model parameters;

[0013] Q200: The materials of the metamaterial are quartz layer, gold layer, polyimide layer, and graphene layer. Quartz is used as the base, metal is laid on it to design the metal array, and other materials are laid on it.

[0014] Q300: A PI layer is coated on a quartz substrate and baked to irradiate the PI. Then, a metamaterial pattern is obtained by standard photolithography, and a gold layer is deposited by FHR magnetron sputtering. The sample is divided into 8mm×8mm pieces by a Disco cutter, soaked in HF for 2min, rinsed with deionized water 3 times, and dried with nitrogen. Graphene is then deposited on the incomplete metal layer to obtain a graphene layer, and finally a terahertz metal-graphene metamaterial sensor is obtained.

[0015] A further improvement of the technical solution of the present invention is that the simulation in the Q100 to obtain the optimal solution model parameters also includes simulating the simulated reflection spectrum of the sensor in the CST MicrowaveStud io software in the Q100, changing the Fermi level of graphene, observing the changes in the reflection spectrum and the changes in the electric field within a frequency range, taking multiple sets of data, using bare metamaterials and composite metamaterials to observe the changes in the reflection spectrum, and determining the optimal solution model parameters, wherein the range of the Fermi level change is 0ev-0.18ev.

[0016] A further improvement of the technical solution of the present invention is that the terahertz metal-graphene metamaterial sensor obtained in the Q300 comprises four layers from bottom to top: quartz, gold, polyimide, and graphene. The thickness of the quartz is 10um, the thickness of the gold is 0.2um, the thickness of the polyimide is 5um, and the thickness of the graphene is 0.1um. Each layer of metamaterial also includes a bottom layer and an incomplete metal structure tightly attached to the bottom layer, a pi layer, and graphene.

[0017] A further improvement of the technical solution of the present invention is that the incomplete metal structure is gold, and is specifically composed of a metal frame, two large rectangles and four small rectangles, wherein the large rectangles are connected to the metal frame through the small rectangles to form a symmetrical pattern, and the small rectangles are at a certain distance from the metal frame.

[0018] A further improvement of the technical solution of the present invention is that the quartz base is a rectangular structure with a length of 70um and a width of 42.9um, the length and width of each layer of the sensor are the same, the inner width of the long side of the metal frame in the incomplete metal structure is 2um and the length is 70um, the inner width of the short side is 2um and the length is 42.9um, the large rectangular metal is 24um long and 37um wide, the small rectangle is 1um away from the metal frame, the small rectangle is 2um long and 0.95um wide, and the small rectangle is 25um away from the metal frame on the left and right.

[0019] A further improvement of the technical solution of the present invention is that the dielectric constant of the quartz base is 3.75, and the conductivity of the incomplete metal structure is 4.561×S / m.

[0020] A further improvement of the technical solution of the present invention is that the other materials in the Q200 include polyimide.

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: after the terahertz wave is incident into the terahertz sensor, the addition of the sample to be tested causes the dielectric environment of the graphene layer to change, thereby observing that the resonant amplitude of the terahertz sensor changes. For the accurate detection of the substance to be tested, the problem of complex processing of traditional detection methods can be solved. By taking the metal-graphene hybrid element sensor as the carrier and using the terahertz technology, the sensitivity of the detection of metaldehyde pesticide in Dendrobium candidum is achieved, and the detection limit reaches 100ng / mL. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the detection steps in the method for determining the concentration of metaldehyde in Dendrobium officinale;

[0023] Figure 2 Schematic diagram of the preparation of the sensor used in the method for determining the concentration of metaldehyde in Dendrobium officinale;

[0024] Figure 3 It is a schematic diagram of the structure sequence of the sensor metamaterial used in the method for determining the concentration of metaldehyde in Dendrobium officinale;

[0025] Figure 4 A side view of a sensor metamaterial used in a method for determining the concentration of metaldehyde in Dendrobium officinale;

[0026] Figure 5 The size and pattern diagram of the incomplete metal in Example 2 and Example 3;

[0027] Figure 6 It is a schematic diagram of the change of electromagnetic resonance of the metamaterial sample at different Fermi levels in graphene in Example 3;

[0028] Figure 7 This is a comparison chart of the transmittance of the bare metamaterial and the metamaterial sample with a graphene layer added in Example 1;

[0029] Figure 8 This is an operation diagram of depositing the metaldehyde solution prepared in Example 1 on a terahertz sensor;

[0030] Fig. 9 It is the reflection spectrum of the metaldehyde solution in Example 1 and the enlarged view of the 1.06-1.28 THz part. DETAILED DESCRIPTION

[0031] Various exemplary embodiments, features and aspects of the present application will be described in detail below with reference to the accompanying drawings. The same reference numerals in the accompanying drawings represent elements with the same or similar functions. Although various aspects of the embodiments are shown in the accompanying drawings, the drawings are not necessarily drawn to scale unless otherwise specified.

[0032] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.

[0033] In addition, in order to better illustrate the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In some examples, methods, means, and elements well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present application.

[0034] Reference Figure 1 - Fig. 9 , the present invention provides three technical solutions:

[0035] Embodiment 1, a method for determining the concentration of metaldehyde in Dendrobium officinale, comprising the following specific steps:

[0036] S100: Use a pipette to drop 20uL of several groups of metaldehyde solutions with different concentrations onto the center of the detection sensor and leave it in the air for 15-20 minutes, waiting for the metaldehyde solution to dry and evaporate on the sensor surface until a thin film is formed and deposited on the 8×8mm 2 On the FSRRs-based sensor formed on the area;

[0037] S200: Test the resonance characteristics of the metamaterial on the sensor through the THz-TDS system. Fix the sensor in the measurement chamber, open the nitrogen valve to dry the measurement chamber, wait for 5-10 minutes, and then scan to obtain the characteristic spectrum of the transmission amplitude.

[0038] S300: By analyzing the relationship between metaldehyde and resonance peak at different concentrations, the concentration of metaldehyde can be accurately detected;

[0039] S400: After each concentration measurement, the metamaterial in the corresponding sensor was soaked in acetone for 10 min to wash away the residual metaldehyde, soaked in anhydrous ethanol for 10 min to wash away the acetone, then rinsed with deionized water for 10 min to wash away the ethanol, and finally dried in a nitrogen-filled environment for the next test.

[0040] In this example, the prepared metaldehyde solution is deposited on the terahertz sensor, as shown in the attached Figure 6 Then, the terahertz wave is incident from the pi layer, and the metaldehyde is attached to the graphene structure. After the terahertz wave is incident, it can couple with the incomplete metal layer to produce a resonant transparent window, thereby obtaining a characteristic spectrum of the transmission amplitude.

[0041] In the study, the LC oscillation model was used to describe the open resonant ring. When the refractive index of the analyte changes, the resonant frequency of the sensor will redshift accordingly. Only the solute metaldehyde after water evaporation is left on the surface of the metamaterial, which shows that the factor affecting the change of the dielectric constant in this experiment is mainly determined by the residual solute metaldehyde. Therefore, the connection of metaldehyde to the THz sensor causes the effective dielectric constant to increase, which causes the resonant frequency to shift to the red.

[0042] Attached Fig. 9 This is the reflection spectrum of metaldehyde solution. The amplitude of the reflection spectrum changes with the concentration and has a strong local response ability at 1.2 THz.

[0043] After adding metaldehyde, the reflection spectrum shows a significant increase. This is because the metaldehyde molecules deposited on the graphene surface cause molecular doping of graphene, thereby affecting the dielectric environment and Fermi level of graphene, causing changes in conductivity, thereby causing the resonant amplitude of the terahertz wave incident on the terahertz detector that detects whether metaldehyde is present to change. The simulated reflection spectrum shows similar results as the Fermi level of graphene changes.

[0044] Therefore, the detection principle of the present invention is that after the terahertz wave is incident on the terahertz sensor, the dielectric environment of the graphene layer is changed by adding the sample to be tested, so that the resonant amplitude of the terahertz sensor is observed to change and the substance to be tested is accurately detected.

[0045] Attached Figure 8 In order to observe more details, when the concentration of tetraacetaldehyde increased from 0 ng / mL to 2400 ng / mL, the part was enlarged to 1.06-1.28 THz, and the resonance peak increased from 1.183 THz to 1.175 THz. As the concentration of tetraacetaldehyde increased, the position of the resonance peak blue-shifted. For liquid samples, the sensor can detect a small amount of tetraacetaldehyde concentration.

[0046] In order to reasonably determine the minimum sensitivity of the metaldehyde solution that the sensor can detect and further study the statistical differences in sensitivity detection, this embodiment performed reflection analysis on 8 metaldehyde solutions of different concentrations.

[0047] Therefore, it was determined that the detection sensitivity of the designed metamaterial combined with the THz-TDS device for tetraacetaldehyde solution was 100 ng / mL, and the designed metamaterial structure could more effectively locally enhance the electromagnetic waves, thereby improving the detection sensitivity.

[0048] Example 2: To specifically detect the concentration of metaldehyde, the sensor preparation process includes the following specific steps:

[0049] Q100: Use CSTM icrowaveStud io software to design a sensor metamaterial model and use the software to perform simulations to obtain the optimal solution model parameters;

[0050] Q200: The materials of the metamaterial are quartz layer, gold layer, polyimide layer, and graphene layer. Quartz is used as the base, metal is laid on it to design the metal array, and other materials are laid on it.

[0051] Q300: A PI layer is coated on a quartz substrate and baked to irradiate the PI. Then, a metamaterial pattern is obtained by standard photolithography, and a gold layer is deposited by FHR magnetron sputtering. The sample is divided into 8mm×8mm pieces by a Disco cutter, soaked in HF for 2min, rinsed with deionized water 3 times, and dried with nitrogen. Graphene is then deposited on the incomplete metal layer to obtain a graphene layer, and finally a terahertz metal-graphene metamaterial sensor is obtained.

[0052] The simulation in the Q100 to obtain the optimal solution model parameters also includes simulating the simulated reflection spectrum of the sensor in the CST MicrowaveStud io software in the Q100, changing the Fermi level of graphene, observing the changes in the reflection spectrum and the changes in the electric field within a frequency range, taking multiple sets of data, using bare metamaterials and composite metamaterials to observe the changes in the reflection spectrum, and determining the optimal solution model parameters, wherein the range of the Fermi level change is 0ev-0.18ev.

[0053] The terahertz metal-graphene metamaterial sensor obtained in the Q300 comprises four layers from bottom to top, namely, quartz, gold, polyimide, and graphene. The thickness of the quartz is 10um, the thickness of the gold is 0.2um, the thickness of the polyimide is 5um, and the thickness of the graphene is 0.1um. Each layer of metamaterial also includes a bottom layer and an incomplete metal structure tightly attached to the bottom layer, a pi layer, and graphene.

[0054] The incomplete metal structure is made of gold, and specifically consists of a metal frame, two large rectangles and four small rectangles, wherein the large rectangles are connected to the metal frame through the small rectangles to form a symmetrical pattern, and the small rectangles are at a certain distance from the metal frame.

[0055] The quartz base is a rectangular structure with a length of 70um and a width of 42.9um. The length and width of each layer of the sensor are the same. In the incomplete metal structure, the inner width of the long side of the metal frame is 2um and the length is 70um, and the inner width of the short side is 2um and the length is 42.9um. The large rectangular metal is 24um long and 37um wide. The small rectangle is 1um away from the metal frame. The small rectangle is 2um long and 0.95um wide. The small rectangle is 25um away from the metal frame on the left and right.

[0056] The dielectric constant of the quartz base is 3.75, the conductivity of the incomplete metal structure is 4.561×S / m, and other materials in the Q200 include polyimide.

[0057] Embodiment 3: As shown in the attached Figure 4 The structure of the metamaterial model shown in the figure includes a bottom layer of quartz, an incomplete metal in close contact, a pi layer and graphene, wherein the dielectric constant of the quartz is 3.75, and the material of the incomplete metal layer is gold, and the conductivity is 4.561×S / m.

[0058] The shape of the incomplete metal layer is as shown in the attached Figure 5 As shown, it is composed of a metal frame, two large rectangles and four small rectangles; the large rectangles are connected to the metal frame through the small rectangles to form a symmetrical figure, and the rectangles are at a certain distance from the metal frame.

[0059] To test the performance of the sensor, Figure 6 The figure shows the change of electromagnetic resonance of graphene at different Fermi levels. It can be seen from the figure that in the range of Fermi levels from 0ev to 0.18ev, the transmittance increases with the increase of Fermi level before 1.05THz, and reaches the trough at 0.95THZ. After 1.05THz, the transmittance decreases with the increase of Fermi level, and reaches the peak at 1.1THz. Therefore, we can change the dielectric environment of graphene to observe the change of electromagnetic resonance, so we take 1.1THz as the frequency to observe its current response on the surface of the metamaterial. Figure 6 The figure shows the current size on the surface of the metamaterial at different Fermi levels, and it is found that the response is strongest at 0 eV. Since the Fermi level can be manipulated by chemical doping, the chemical substances doped on the graphene surface can affect the graphene dielectric constant, thereby affecting the change of the Fermi level. Therefore, the surface current of the metamaterial sensor can be observed to achieve accurate detection.

[0060] Figure 7 The figure shows the transmittance comparison between the bare metamaterial and the metamaterial sample with added graphene layer. This shows that graphene has a considerable influence on the transmittance of the metamaterial. Using the graphene layer as the top layer has a huge impact on the response of the metamaterial sample to the terahertz wave. It also shows that the addition of the graphene layer makes the terahertz sensor composed of the metamaterial sample more sensitive to the terahertz wave.

[0061] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0062] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for determining the concentration of metaldehyde in Dendrobium officinale, characterized in that: The specific steps include: S100: Use a pipette to drop 20uL of several groups of metaldehyde solutions with different concentrations onto the center of the detection sensor and leave it in the air for 15-20 minutes, waiting for the metaldehyde solution to dry and evaporate on the sensor surface until a thin film is formed and deposited on the 8×8mm 2 On the FSRRs-based sensor formed on the area; S200: Test the resonance characteristics of the metamaterial on the sensor through the THz-TDS system. Fix the sensor in the measurement chamber, open the nitrogen valve to dry the measurement chamber, wait for 5-10 minutes, and then scan to obtain the characteristic spectrum of the transmission amplitude. S300: By analyzing the relationship between metaldehyde and resonance peak at different concentrations, the concentration of metaldehyde can be accurately detected; S400: After each concentration measurement, the metamaterial in the corresponding sensor was soaked in acetone for 10 min to wash away the residual metaldehyde, soaked in anhydrous ethanol for 10 min to wash away the acetone, then rinsed with deionized water for 10 min to wash away the ethanol, and finally dried in a nitrogen-filled environment for the next test.

2. The method for determining the concentration of metaldehyde in Dendrobium officinale according to claim 1, characterized in that: In order to specifically detect the concentration of metaldehyde, the sensor preparation process includes the following specific steps: Q100: Use CSTMicrowaveStudio software to design the sensor metamaterial model and use the software to simulate and obtain the optimal solution model parameters; Q200: The materials of the metamaterial are quartz layer, gold layer, polyimide layer, and graphene layer. Quartz is used as the base, metal is laid on it to design the metal array, and other materials are laid on it. Q300: A PI layer is coated on a quartz substrate and baked to irradiate the PI. The metamaterial pattern is then obtained by standard photolithography. A gold layer is deposited by FHR magnetron sputtering. The sample is cut into 8 mm × 8 mm pieces using a Disco cutter, soaked in HF for 2 min, rinsed with deionized water three times, and dried with nitrogen. Graphene is then deposited on the incomplete metal layer to obtain a graphene layer, and finally a terahertz metal-graphene metamaterial sensor is obtained.

3. The method for determining the concentration of metaldehyde in Dendrobium officinale according to claim 2, characterized in that: The simulation in the Q100 to obtain the optimal solution model parameters also includes simulating the simulated reflection spectrum of the sensor in the CSTMicrowaveStudio software in the Q100, changing the Fermi level of graphene, observing the changes in the reflection spectrum and the changes in the electric field within a frequency range, taking multiple sets of data, using bare metamaterials and composite metamaterials to observe the changes in the reflection spectrum, and determining the optimal solution model parameters, wherein the range of the Fermi level change is 0ev-0.18ev.

4. The method for determining the concentration of metaldehyde in Dendrobium officinale according to claim 1, characterized in that: The terahertz metal-graphene metamaterial sensor obtained in the Q300 comprises four layers from bottom to top, namely, quartz, gold, polyimide, and graphene. The thickness of the quartz is 10um, the thickness of the gold is 0.2um, the thickness of the polyimide is 5um, and the thickness of the graphene is 0.1um. Each layer of metamaterial also includes a bottom layer and an incomplete metal structure tightly attached to the bottom layer, a pi layer, and graphene.

5. The method for determining the concentration of metaldehyde in Dendrobium officinale according to claim 4, characterized in that: The incomplete metal structure is made of gold, and specifically consists of a metal frame, two large rectangles and four small rectangles, wherein the large rectangles are connected to the metal frame through the small rectangles to form a symmetrical pattern, and the small rectangles are at a certain distance from the metal frame.

6. The method for determining the concentration of metaldehyde in Dendrobium officinale according to claim 5, characterized in that: The quartz base is a rectangular structure with a length of 70um and a width of 42.9um. The length and width of each layer of the sensor are the same. In the incomplete metal structure, the inner width of the long side of the metal frame is 2um and the length is 70um, and the inner width of the short side is 2um and the length is 42.9um. The large rectangular metal is 24um long and 37um wide. The small rectangle is 1um away from the metal frame. The small rectangle is 2um long and 0.95um wide. The small rectangle is 25um away from the metal frame on the left and right.

7. The method for determining the concentration of metaldehyde in Dendrobium officinale according to claim 6, characterized in that: The dielectric constant of the quartz base is 3.75, and the electrical conductivity of the incomplete metal structure is 4.561×S / m.

8. The method for determining the concentration of metaldehyde in Dendrobium officinale according to claim 2, characterized in that: Other materials in the Q200 include polyimide.